Coming of Age on the Margins: A Life Course Perspective on the Time Use of Australian Adolescents with Disabilities - O'Flaherty, Martin (My University, 2023)
People with disabilities experience persistent, multifaceted disadvantage across the life course. The origins of life course disadvantage among people with disabilities may stem, in part, from exclusion during developmentally sensitive periods in childhood. Time use among adolescents represents a potentially important mechanism implicated in the emergence of disability-related disadvantage, but previous research has largely neglected the time use of school age adolescents with disabilities. Utilizing nationally representative time diary data, this study investigated disability-related differences in adolescents’ time use, and how these gaps vary by sex and age. Results indicated that disability-related differences in time use are widespread and substantial in magnitude. Adolescents with disabilities spend more time in screen-based leisure, alone, and with mothers, and less time in educational activities than non-disabled adolescents. Boys with disabilities additionally spend less time in structured leisure and with peers than non-disabled boys. Differences in time alone, with peers, and in screen-based leisure increase in magnitude at older ages. We conclude that differential time use in adolescence may contribute to multiple persistent disadvantages experienced by people with disabilities over the life course.
Social Forces
Keywords: Adolescents and youth; Childhood and child development; Health and wellbeing; Learning, education and training; Social engagement